2020
DOI: 10.1093/ehjci/jeaa004
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences and higher upper normal limits for left atrial end-systolic volume in individuals in their mid-60s: data from the ACE 1950 Study

Abstract: Aims The current study aimed to describe normal values of left atrial (LA) volumes and LA emptying fraction (LAEF) in a large sample in their mid-60s from the general population and to explore sex differences. Methods and results In the Akershus Cardiac Examination (ACE) 1950 Study, body surface area-indexed LA maximum (LAVimax) and minimum (LAVimin) volumes and LAEF were measured in 3489 individuals aged 63.9 ± 0.6 years fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 42 publications
1
7
0
Order By: Relevance
“…We also found a higher correlation coefficient between NT-proBNP and LAVi min than LAVi max . However, as previously shown in our material,30 LAVi min has both higher intra-observer and inter-observer variability than LAVi max . Although this increased variability was not found in the study by Olsen et al ,10 the otherwise lack of normal values and less prospective data do not currently support the superior clinical usefulness of LAVi min compared with LAVi max .…”
Section: Discussionsupporting
confidence: 86%
“…We also found a higher correlation coefficient between NT-proBNP and LAVi min than LAVi max . However, as previously shown in our material,30 LAVi min has both higher intra-observer and inter-observer variability than LAVi max . Although this increased variability was not found in the study by Olsen et al ,10 the otherwise lack of normal values and less prospective data do not currently support the superior clinical usefulness of LAVi min compared with LAVi max .…”
Section: Discussionsupporting
confidence: 86%
“…2,21 In contrast, age and endurance exercise are related to LA enlargement even in absence of LA disease. 22,23 Prevention of LA dysfunction and treatment of LA disease may therefore be of critical importance. The relationship between changes in LV structure and function and subsequent CV outcome is well established.…”
Section: Introductionmentioning
confidence: 99%
“…Recent data suggest that timely therapeutic intervention may attenuate the process of deleterious LA remodelling and potentially promote reverse LA remodelling with a consequent improvement in clinical symptoms and outcomes 2,21 . In contrast, age and endurance exercise are related to LA enlargement even in absence of LA disease 22,23 …”
Section: Introductionmentioning
confidence: 99%
“… 22 We have previously shown that in a healthy subgroup of this general population at ages 62 to 65 years, men had larger LA volumes indexed for body surface area compared with women. 23 However, most studies of normal LA volumes have not identified clinically significant differences between the sexes, and sex‐specific cutoffs have not been endorsed. 24 …”
Section: Discussionmentioning
confidence: 99%